Tensile response of adhesively bonded composite-to-composite single-lap joints in the presence of bond deficiency - Bhanushali, R.; Ayre, David; Yazdani Nezhad, Hamed (Elsevier, 2017)
This paper studies the quasi-static tensile response of adhesively bonded composite-to-composite single-lap joints in the presence of weak and kissing bonds, as an attempt for characterisation of bond deficiencies likely to occur in polymer composite bonded repair. Cytec FM®94 adhesive film (0.25 mm nominal thickness) was used for all joints to bond two 2mm-thickness carbon fibre polymer composite laminates manufactured from unidirectional Hexcel M21/T800S pre-pregs. Peel-ply surface treatment was used for all joints. The bonds were deteriorated via five methods: pre-curing the centre of bond area prior to the cure of the bond edges, increasing the curing temperature rate, reducing the curing time, and embedding PTFE films over the centre of the bond. For the last method, the studies were carried out by embedding PTFE films on one and two sides of the adhesive film. The bond deterioration was followed by non-destructive inspections using ultrasound C-scanning. The ultimate failure load of the joints with defected bonds (i.e. weak and kissing bonds) was measured and compared to that of the joints with no defect (i.e. good bonds). It was found that rapid curing and short-time curing reduces more than 50% of the load carrying capacity of the single-lap joins in tension while the joints with weak bonds introduced by pre-curing of a large area of the bond (>60%) can take up more than 65% of the ultimate load of the joint with good bond. Also, optical microscopy of the bond surfaces after failure showed changes in failure type for the rapid and short-time cure, strongly correlated with their significant failure load reduction.
Keywords: Single-lap joint; Weak bond; Degree of cure; Composite repair; Rapid cure